(untitled) (Research, Society and Development, 2021)
The aim of the present study was to identify the existing literature related to anxiety in adolescents in the context of the COVID-19 pandemic. As a methodology used to write this article was the systematic review of the literature with researched material that was available in the MEDLINE and Pubmed databases, available in a completely free form, published from 2020. The results were composed with a discussion of 16 articles that were selected after thorough reading and analysis of the content. For a better organization of the discussion of results, the data were divided into three specific topics, with grouping them according to the theme related to the information, as follows: 1) Prevention of anxiety in adolescents facing the pandemic by COVID-19; 2) Characteristics of anxiety in adolescents facing the pandemic by COVID-19; 3) Innovative strategies in medical interventions in adolescents with anxiety in the face of the COVID-19 pandemic. It is concluded that anxiety was very prevalent among adolescents during the outbreak of COVID-19, since such a pandemic generated a multiplying effect on several characteristics of anxiety. It is important for health authorities to identify groups at high risk for mental illness in order to implement appropriate psychiatric and psychological interventions. There is still little literature that focuses on anxiety in adolescents during the pandemic. It is necessary, therefore, that new studies with a focus on anxiety reduction strategies associated with this world context emerge, in order to minimize the negative impact on adolescents’ quality of life.